Individual and Combined Effects of Melamine and Cyanuric Acid in Young Pekin Ducks - Landers, B.R.; Murarolli, R.A.; Gelven, R.E.; Brand, L.M.; Kobashigawa, E.H.; Ledoux, D.R.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2013)
An experiment was conducted with Pekin ducks to determine the toxicity of melamine (MEL) and cyanuric acid (CYA) in ducks fed treatments from day 3 to day 21 of age. Two hundred and twenty three three-day-old male ducks were assigned to one of 10 treatment groups. Treatments included: (1) a basal diet (BD) containing no MEL or CYA; (2) BD+0.5% MEL; (3) BD+1.0% MEL; (4) BD+1.5% MEL; (5) BD+0.5% CYA; (6) BD+1.0% CYA; (7) BD+1.5% CYA; (8) BD+0.5% MEL+0.5% CYA; (9) BD+1.0% MEL+1.0% CYA and (10) BD+1.5% MEL+1.5% CYA. Control and treatments fed MEL alone or MEL+CYA were fed to 5 pens of 5 ducks each. Treatments fed CYA alone were fed to 4 pens of 4 ducks each. Compared to controls, birds fed > 1.0% MEL had lower (P